Anesthesia-related mortality in pediatric patients: a systematic review (Clinics, 2012)
This systematic review of the Brazilian and worldwide literature aimed to evaluate the incidence and causes of perioperative and anesthesia-related mortality in pediatric patients. Studies were identified by searching EMBASE (1951-2011), PubMed (1966-2011), LILACS (1986-2011), and SciElo (1995-2011). Each paper was revised to identify the author(s), the data source, the time period, the number of patients, the time of death, and the perioperative and anesthesia-related mortality rates. Twenty trials were assessed. Studies from Brazil and developed countries worldwide documented similar total anesthesia-related mortality rates (